Pengaruh Kualitas Pelayanan Dan Harga Terhadap Keputusan Pembelian Konsumen Pada Aplikasi Belanja Online Shopee Di Desa Kedung Jeruk - Aripin, Moh Zaenal; Isyanto, Puji; Sumarni, Neni (Jurnal Manajemen DIVERSIFIKASI, 2023)
Shopee is an online shopping application that has high purchasing decision expectations. Inan effort to achieve these high purchasing decision expectations, the online shoppingapplication Shopee must pay attention to the quality of their online customer service. Servicequality has an important role in influencing consumer interest to buy a product. Good servicequality will spur consumers to buy products or make purchasing decisions (Idriyanti,2013:20). Service quality is the level (ability) of the seller in providing everything that thecustomer expects to meet their needs. Of the various services provided by the online shoppingapplication Shopee, Online customer service is a service component that is often used byconsumers. Online customer service is a facility provided by the company to help consumers.Some of the services provided by online customer service to consumers, such as respondingto calls from consumers, direct chat services that can be done via the website, customerservice via email, and others.